Stakeholder‐derived recommendations and actions to support deep‐reef conservation in the Western Indian Ocean. Issue 1 (27th October 2022) - Stefanoudis, Paris V.; Talma, Sheena; Fassbender, Nico; Swanborn, Denise; Ochieng, Christine Nyangweso; Mearns, Kevin; Komakoma, John D.; Otwoma, Levy M.; Mbije, Nsajigwa Emmanuel; Osuka, Kennedy E.; Samoilys, Melita; Shah, Nirmal; et al.
Abstract: Deep reefs below 30 m provide essential ecosystem services for ocean health and human well‐being such as food security and climate change resilience. Yet, deep reefs remain poorly researched and largely unprotected, including in the Western Indian Ocean (WIO). Here, we assessed current conservation approaches in the WIO focusing on deep reefs, using a combination of online surveys and semi‐structured interviews. Results indicated that deep‐reef data are sparse and commonly stemming from non‐peer‐reviewed or non‐publicly available sources, and are often not used to inform conservation of WIO marine protected areas. Based on those findings, we co‐developed a framework with WIO stakeholders comprising recommendations linked to specific actions to be undertaken by regional actors to improve the capacity of the region to collect and share deep‐reef information. We hope this framework will enhance deep‐reef stewardship and management throughout the WIO and thus aid sustainable blue economic growth in the region.